Smart logistics transformation collaboration between manufacturers and logistics service providers: A supply chain contracting perspective - Weihua Liu (Journal of Management Science and Engineering, 2021)
Intelligent transformation of manufacturers requires smart logistics transformation collaboration, which improves competitiveness. In this study, we construct a Stackelberg game model based on the mutual influence and restriction in the relationship between a manufacturer and a logistics service provider (LSP) undergoing smart logistics transformation. We investigate whether cost-sharing (CS) or revenue-sharing (RS) contracts can coordinate the supply chain and suggest a hybrid CS–RS contract to improve performance. We find that, compared with decentralized options, CS and RS contracts achieve a higher level of smart logistics transformation. While the coordination and effectiveness of CS contracts are superior to those of RS contracts, neither can fully coordinate the supply chain. The proposed hybrid CS–RS contract allows the manufacturer to share the LSP’s costs before the transformation and its partial revenue after transformation, so that the LSP can reduce its service charge, thereby achieving full supply chain coordination.